THE INTEGRATION OF DIGITAL ERA SPIRITUAL EDUCATION AND ITS INFLUENCE ON THE PERSONALITY OF STUDENTS OF MADRASAH TSANAWIYAH NEGERI 1 LUBUK LINGGAU - Alia, Defi; Saepudin, Saepudin; S, Zulkarnain (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Background: The growing emphasis on character development in education necessitates a closer examination of spiritual education's role in shaping students' personalities. Purpose: This study investigates its impact within the context of Madrasah Tsanawiyah Negeri 1 Lubuk Linggau. This study aims to analyze the influence of the application of spiritual education on the personality of students of Madrasah Tsanawiyah Negeri 1 Lubuk Linggau Indonesia. Method: The research method used is a quantitative type method. This type of method was chosen because it is in accordance with the purpose of the study, which is to test two variables against affect. The variable to be tested is variable x the application of spiritual education and variable y is the character of students. The population was 200 students and a sample size of 2.5 percent was obtained as many as 50 students. Meanwhile, the research data produced through the questionnaire was tested using the SPSS-assisted moment product correlation formula. Result: The results of the data analysis carried out showed that the calculation was 0.58 > the table was 0.1966 with an error level of 0.05 and the amount of N = 100. The results of the interpretation of the level of relationship to the price of the correlation coefficient of the two variables show a rather low level of relationship. Conclusion: The results indicated a significant influence and showed that the more intensive the application of spiritual education used in the learning process, the higher the personality of students. The results are also a reference for teachers to improve Islamic learning by applying a spiritual education approach to students so that they can achieve a better personality.